2019
DOI: 10.1136/jech-2018-211815
|View full text |Cite
|
Sign up to set email alerts
|

Low stress resilience in late adolescence and risk of smoking, high alcohol consumption and drug use later in life

Abstract: BackgroundWhile compromised stress resilience constitutes a recognised risk factor for somatic and psychiatric disease development in general, the knowledge about how individual variation in vulnerability to stress may specifically influence the long-term risks of disadvantageous health behaviours is limited.MethodsIn this Swedish cohort study, we aimed to investigate the association between stress resilience in late adolescence and adult use of addictive substances. We included 9381 men with information on ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…These data suggest that the higher the students' resilience, the lower their tendency to abuse drugs. These results are consistent with those of Mohammadi, Aghajani et al [18], and Kennedy, Chen, Fang, and associates [19].…”
Section: Discussionsupporting
confidence: 93%
“…These data suggest that the higher the students' resilience, the lower their tendency to abuse drugs. These results are consistent with those of Mohammadi, Aghajani et al [18], and Kennedy, Chen, Fang, and associates [19].…”
Section: Discussionsupporting
confidence: 93%
“…A large cohort study followed children for 16 years and found that girls with high stress at age three had over two times higher odds than girls with low stress to start smoking early 16 . Another large cohort study showed that low stress resilience in late adolescence increased the risk of smoking in adulthood 17 . A population-based cross-sectional study, measuring stress with the same tool as our study, found that a one-unit increase in perceived stress was associated with in a significant 5% increased odds of smoking 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Men who lost their parents were slightly less likely to get a long education (not shown). It is possible that they were more often smokers as well (Kennedy et al, 2019). We considered the possibility that they also tended to partner women with a lower education which, in turn, could correlate with health behaviours (smoking in pregnancy being the factor with the strongest potential to affect next generation's birth weight).…”
Section: Discussionmentioning
confidence: 99%